Intrahepatic bacterial metataxonomic signature in non-alcoholic fatty liver disease - Sookoian, Silvia Cristina (2020)
Objective: We aimed to characterise the liver tissue bacterial metataxonomic signature in two independent cohorts of patients with biopsy-proven non-alcoholic fatty liver disease (NAFLD) diagnosis, as differences in the host phenotypic features - from moderate to severe obesity - may be associated with significant changes in the microbial DNA profile. Design and methods: Liver tissue samples from 116 individuals, comprising of 47 NAFLD overweight or moderately obese patients, 50 NAFLD morbidly obese patients elected for bariatric surgery and 19 controls, were analysed using high-throughput 16S rRNA gene sequencing. Results: Liver bacterial DNA profile significantly differs between morbidly obese and non-morbidly obese patients with NAFLD. Bacteroidetes (p=1.8e-18) and Firmicutes (p=0.0044) were over-represented in morbidly obese patients and Proteobacteria (p=5.2e-10) - specifically Gammaproteobacteria and Alphaproteobacteria, and Deinococcus-Thermus (p=0.00012) - were over-represented in the non-morbidly obese cohort. Cohort-specific analysis of liver microbial DNA signatures shows patterns linked to obesity. The imbalance in Proteobacteria (Alpha or Gamma) among non-morbidly obese patients, and Peptostreptococcaceae, Verrucomicrobia, Actinobacteria and Gamma Proteobacteria DNA among morbidly obese patients was associated with histological severity. Decreased amounts of bacterial DNA from the Lachnospiraceae family were associated with more severe histological features. Proteobacteria DNA was consistently associated with lobular and portal inflammation scores. Microbial DNA composition corresponded to predicted functional differences. Conclusion: This is the first comprehensive study showing that the liver tissue of NAFLD patients contains a diverse repertoire of bacterial DNA (up to 2.5×104 read counts). The liver metataxonomic signature may explain differences in the NAFLD pathogenic mechanisms as well as physiological functions of the host.